1998
DOI: 10.1111/j.1530-0277.1998.tb03666.x
|View full text |Cite
|
Sign up to set email alerts
|

Common Quantitative Trait Loci for Alcohol‐Related Behaviors and CNS Neurotensin Measures: Voluntary Ethanol Consumption

Abstract: The C57BL/6, DBA/2, and recombinant inbred (RI) strains derived from them (BxD RIs) are the most frequently studied mouse strains with regard to genetic regulation of voluntary ethanol consumption (YEC). We have studied VEC in an alternate genetic model provided by the LSxSS RIs. These RI strains exhibit phenotypic extremes in VEC comparable to the C57BL/6 and DBA/2 mice and genotype-dependent sex differences in drinking behavior. A correlational analysis between various ethanol-related behaviors suggests gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 59 publications
(5 reference statements)
1
23
0
Order By: Relevance
“…Finally, it is possible that tolerance and drinking are genetically related in rats but not in mice. Indeed, previous studies in mice have shown little genetic co-variation between alcohol preference and measures of tolerance (Gehle and Erwin 1998, but see Erwin et al 1980). Further studies would have to be done to assess this potential species difference.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, it is possible that tolerance and drinking are genetically related in rats but not in mice. Indeed, previous studies in mice have shown little genetic co-variation between alcohol preference and measures of tolerance (Gehle and Erwin 1998, but see Erwin et al 1980). Further studies would have to be done to assess this potential species difference.…”
Section: Discussionmentioning
confidence: 96%
“…Several overlapping regions on chromosome 15 were identified as QTL acting on ethanol consumption in previous studies (Gehle & Erwin, 1998 ;Phillips et al 1998 ;Tarantino et al 1998 ;Vadasz et al 2000a, b).…”
Section: Genetics Of Ethanol Responses 165mentioning
confidence: 88%
“…Previously trait-related QTL on the chromosome : 1 Htas1, 83.6 cM (Crabbe, 1994) ; 2 Ap7q, 25 cM (MGI) ; 3 Htas6, 60 cM (Crabbe, 1994) ; 4 Htas5, 63 cM (Crabbe, 1994) (Gill et al 1996) ; 14 EtOH preference QTL, 4 cM (Gill et al 1998) ; 15 Drb7, 45 cM, Lore5, 46 cM (MGI), EtOH consumption QTL (Gehle & Erwin, 1998 ;Phillips et al 1998 ;Tarantino et al 1998 ;Vadasz et al 2000 a, b).…”
Section: Chronic Ethanol Consumption and Withdrawalmentioning
confidence: 97%
“…The activation of dopamine neurotransmission in the nucleus accumbens is thought to be involved in the motivational and reward properties of alcohol and other abused drugs [Koob and Le Moal, 1997;Tanda et al, 1997]. Recent quantitative trait loci studies of mouse models of alcoholism [Gehle and Erwin, 1998;Phillips et al, 1994;Tarantino et al, 1998] found linkage between the D 2 dopamine receptor (DRD2) gene and alcohol preference, suggesting a genetic basis for this behavior. Moreover, studies of genetically manipulated animals further support a role for the dopaminergic system in alcohol and other drugs of abuse.…”
mentioning
confidence: 99%